Internal browning alleviation of Queen pineapple cv. 'Sawi' under cold storage using salicylic acid or abscisic acid peduncle infiltration. Issue 6 (2nd November 2019) - Youryon, Pannipa; Supapvanich, Suriyan; Wongs-Aree, Chalermchai
ABSTRACT: Internal browning (IB) is a main problem of Queen pineapple during cold storage. The effects of exogenous salicylic acid (SA) or abscisic acid (ABA) on IB alleviation of the pineapple during cold storage were investigated. 'Sawi' pineapples were peduncle-infiltrated with 2 mM SA or 380 µM ABA for 3 d at 13°C followed storage at 13°C for 14 d. IB incidence and IB-related factors including lipid peroxidation, antioxidant capacity and antioxidant enzymes activities of the tissue adjacent to core were investigated after storage for 7 and 14 d followed by 2 d at room temperature (RT). Both SA and ABA treatments obviously alleviated IB development. ABA lowered TP content, MDA accumulation and the activities of LOX, PAL and PPO and induced POD activity. SA lowered PAL and PPO activity, delayed LOX activity and MDA increase, enhanced phenols, antioxidant activity and both antioxidant enzyme yields. Both ABA and SA peduncle infiltration alleviated IB incidence of Queen pineapple during cold storage. Although ABA could reduce the IB incidence better than SA, due to the efficiency of lower reactions of browning-related enzymes and lipid peroxidation, exogenous SA application might be a better choice for commercial use. Abbreviations: Total phenols (TP), Malondialdehyde (MDA), Lipoxygenase (LOX), Phenylalanine ammonia lyase (PAL), Polyphenol oxidase (PPO), Peroxidase (POD) and Internal browning (IB)